Diastereoselective Construction of trans-2-Alkyl-6-aryl-3,6-dihydro-2H-pyrans via Dehydrogenative Cycloetherification Promoted by DDQ - Yu, Heesun; Lee, Ryangha; Kim, Hyoungsu; Lee, Dongjoo (Organic Letters, 2021)
A diastereoselective synthesis of trans-2-alkyl-6-aryl-3,6-dihydro-2H-pyrans has been described. Dehydrogenative cycloetherification of (E)-(±)-1-aryl-5-hydroxy-1-alkenes promoted by DDQ proceeded cleanly via 6-endo cyclization to afford trans-2-alkyl-6-aryl-3,6-dihydro-2H-pyrans (32 examples) in good yield (up to 89%) and with moderate to excellent diastereoselectivity (up to 99:1). The synthetic utility of the method was illustrated by the second total synthesis of (±)-(2R,6S)-3,4-dehydro-1,7-bis(4-hydroxy phenyl)-4′de-O-methyl centrolobine and a total synthesis of (±)-centrolobine.